Evaluasi dan Penyesuaian Sistem Ventilasi Pada Tambang Batubara Bawah Tanah Lubang 02 PT.Cahaya Bumi Perdana, Kota Sawahlunto, Provinsi Sumatera Barat. - Rizki Putri Bungo; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2020)
Abstract.PT.Cahaya Bumi Perdana is one of the underground coal mining companies in Sawahlunto City that applies the room and pillar mining method. The ventilation system used is a forcing system by arranging the blower in a relay. The blower system installation is not followed by the suction blower installation, so that dirty air is not immediately circulated out. Dirty air resulting from mining activities from one front is pumped back to the next front and increases the increase in dust density and temperature. From the results of temperature measurements in the main 02 hole (L02U) 28.6ºc and in the accompaniment 02 hole (L02P) 26.9ºc. The average humidity in L02U is 91.4% and in L02P 90.3%. This is contrary to government regulations in Kepmen 1827 K / 30 / MEM / 2018 which states "Air temperatures in underground mines must be maintained between 18ºc to 24ºc with a maximum relative humidity of 85%" so evaluation must be carried out. The total air requirement for mining activities in L02U is 12.6032 m3 / sec and in the L02P hole is 11.3205 m3 / sec. To meet these needs, the main hole requires 9 blowers and the accompanying hole needs 6 blowers, so that each hole must be added by 1 blow blower. In order to make the hole condition more comfortable, it needs to be added with a suction fan unit to accelerate the transportation of dirty air to the outside of the hole. Ventilation system modeling produces 3D ventilation system models before and after the addition of a blower. Keywords: Blower, Temperature, Humidity, Speed, Evaluation, Ventilation System Modeling